Contando histórias: a interpretação livre de textos ou a ausência do método de análise de dados na pesquisa qualitativa - Samuel de Carvalho Lima (Discimus: Revista Digital de Educación)
The text problematizes the widespread tendency in qualitative research in Education and Language Studies to replace rigorous data analysis with free interpretations—practices the author refers to as “storytelling.” It argues that although the interpretivist perspective acknowledges the subjective and contextual nature of knowledge, this does not exempt the researcher from explicitly stating the method by which data interpretation is carried out. The lack of such explicitness undermines the internal coherence of the research and weakens its academic evaluation by peers. As a methodological alternative, the author proposes Dialogical Discourse Analysis, grounded in the thought of Bakhtin and the Moscow Circle, which enables the analysis of dialogical relations between subjects through their utterances. Lima emphasizes that this stance must be explicitly detailed in the theoretical-methodological section and warns that its omission compromises the scientific integrity of qualitative research.